Pelatihan Penyusunan Laporan Keuangan Sederhana Untuk Usaha Tani Dan Ternak Di Gampong Teupin Panah Kecamatan Kaway XVI Kabupaten Aceh Barat - Lilis Marlina (Jurnal Pengabdian Agro and Marine Industry, 2022)
This community service aims to improve the knowledge and skills of farmers and livestock business actors in compiling simple financial reports that can be used as a basis for decision making. The target of the service is farming and livestock business actors in Teupin Panah Village, Kaway XVI District. The problems faced were resolved in three stages, namely the preparation, implementation, and evaluation stages. Preparation is carried out by conducting a preliminary survey to see conditions in the field regarding the implementation of the preparation of simple financial statements by farmers and livestock businesses. The implementation stage is carried out through training using the lecture method, namely by presentation techniques, followed by discussion or question and answer. While the evaluation stage is carried out simultaneously with the training process. The results of the training activities show that the farmers and livestock business actors are very enthusiastic about participating in the training and are satisfied with the material provided so that in the following year it is hoped that there will be further activities to support the improvement of farming and livestock.